Perceived social support and psychological well-being among patients with epilepsy - Nazia Nazir; Muhammad Salman Zafar; Muhmmad Numan Akram; Maryam Khokhar; Iqra Yousaf (Journal of the Pakistan Medical Association, 2023)
This cross-sectional study aimed to explore the relationship between perceived social support and psychological well-being in patients with epilepsy. The study was conducted, from January to December 2019, after ethical approval from the research ethical committee of FMU (Faisalabad Medical University, Faisalabad). A sample of 90 patients, attending free epilepsy camp in Mujahid Hospital Madina Town Faisalabad and psychiatry OPD of government General hospital G.M. Abad Faisalabad, was collected by using the Multidimensional Scale of Perceived Social Support (Urdu version). Moreover, Psychological well-being was assessed by Ryff Scale. Statistical analysis was done through data Correlation and T-test SPSS version 21. A positive correlation between psychological well-being and perceived social support in epileptic patients was established (p<0.001). —Continue